If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -6r = 6r(4 + -1r) 24 + -6r = (4 * 6r + -1r * 6r) 24 + -6r = (24r + -6r2) Solving 24 + -6r = 24r + -6r2 Solving for variable 'r'. Combine like terms: -6r + -24r = -30r 24 + -30r + 6r2 = 24r + -6r2 + -24r + 6r2 Reorder the terms: 24 + -30r + 6r2 = 24r + -24r + -6r2 + 6r2 Combine like terms: 24r + -24r = 0 24 + -30r + 6r2 = 0 + -6r2 + 6r2 24 + -30r + 6r2 = -6r2 + 6r2 Combine like terms: -6r2 + 6r2 = 0 24 + -30r + 6r2 = 0 Factor out the Greatest Common Factor (GCF), '6'. 6(4 + -5r + r2) = 0 Factor a trinomial. 6((1 + -1r)(4 + -1r)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(1 + -1r)' equal to zero and attempt to solve: Simplifying 1 + -1r = 0 Solving 1 + -1r = 0 Move all terms containing r to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1r = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1r = 0 + -1 -1r = 0 + -1 Combine like terms: 0 + -1 = -1 -1r = -1 Divide each side by '-1'. r = 1 Simplifying r = 1Subproblem 2
Set the factor '(4 + -1r)' equal to zero and attempt to solve: Simplifying 4 + -1r = 0 Solving 4 + -1r = 0 Move all terms containing r to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1r = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1r = 0 + -4 -1r = 0 + -4 Combine like terms: 0 + -4 = -4 -1r = -4 Divide each side by '-1'. r = 4 Simplifying r = 4Solution
r = {1, 4}
| 3x-5(x-6)=2(x-10) | | 7b-5=37 | | 11(v+2)-2v=3(3v+4)-20 | | 13/4(-x-4/3)+17/4x=3/2x-151/30 | | 2x+40=(2/11)x | | 7y-24=10 | | 8.2n+4.1=32.8 | | 16x-15-9x=18 | | 4(3-1)-2= | | 1/4+7=13 | | 0.05x+0.06(200-x)=11.6 | | -6x-(-1x+6)=(x-2)-4(3x-6) | | f(x)=x^2+8x+20 | | 1/3*(x+2)-1/5*(x-3)=4 | | 2m/m+3/m=1 | | 1/9y+1/3=-2/27 | | 14x=37 | | y=4(x-7)+6 | | 0.005(x+3)=0.006x+0.011 | | -2(x-4)=13 | | 5x-10x-2x=18 | | 2+(-4)+(-x)-4-(-1)=(-2)+(-x)-4 | | 2(x-b)=x | | 3n+8.8=29.8 | | 2x+21x+28=97 | | 44=4x+4x+9 | | -7-2(m)+1/2(m)=4(m)-10 | | 6x-8=8x+8 | | -2/3(2x+9)=1/3(-4x-54)+12 | | x+5/(x-5)=5+5/(x-5) | | -x+11=-3.4+x | | 1/x-1=7/x+5 |